SISTEM PENDUKUNG KEPUTUSAN BERBASIS WEB UNTUK MENENTUKAN KONSENTRASI JURUSAN SISWA DENGAN METODE LOGIKA FUZZY TSUKAMOTO (STUDI KASUS : MADRASAH ALIYAH WATHONIYAH ISLAMIYAH KARANGDUWUR PETANAHAN KEBUMEN) - Mujtahidatun Khusna Sabil; Dina Andayati; Mohammad Sholeh (Jurnal SCRIPT, 2016)
The determination of student's concentration is one of activities need to be conducted every year at Madrasah Aliyah Wathoniyah Islamiyah Karang duwur. The final output of the determination process is each student will be recommended to take whether science or social class. The existing system of the determination process, so far, has not been computerized yet.One of the system that could be applied in this case is decision support system with a certain method and a supporting tool. The method applied in this case is Tsukamoto fuzzy logic method. This method was chosen due to its simplicity, more tolerant with inappropriate data, and compatible to be applied in the case. Whereas, the tool used in this case is PHP programming language.The system would help the teachers to determine the students' major concentration. It will offer an output in sort of quality value for the students to join whether science or social class. Furthermore, the quality value can be used in the process of decision making. With the existence of the sytem, it is highly expected that the decision making process will be easier and quicker to be done.